Complement in hidradenitis suppurativa. (1st August 2018) - Kanni, T.; Zenker, O.; Habel, M.; Riedemann, N.; Giamarellos‐Bourboulis, E.J.
Summary: This is a study on the pathogenesis (causes) of hidradenitis suppurativa (HS). HS is a common skin disorder that affects almost 1% of people in Europe. It manifests with boils in areas of the skin rich in sweat glands like the axilla (arm pits), the breast, the groins and the buttocks. These boils progressively enlarge and rupture with the production of pus and blood. Stress usually proceeds this process. This study was undertaken at the University Hospital of Athens in Greece. The authors measured the concentrations of C5a and C5b‐9 in the plasma (blood) of patients with HS. The rationale for their study was that C5a causes the influx of neutrophils and the formation of pus. It was found that C5a and C5b‐9 are largely elevated in HS and that this is associated with HS severity, so higher levels of C5a and C5b‐9 are linked with worse HS symptoms. Interestingly, the authors describe that C5a stimulates the over‐activation of monocytes, which are cells causing inflammation. Based on this finding, the authors suggest that over‐production of C5a is a newly discovered pathway for the pathogenesis of HS. The authors also show how the drug IFX‐1, that selectively blocks C5a function, decreases the activation of monocytes and may become a promising new medicine for the treatment of HS.